PWE-366 The bowel cancer screening programme (bcsp) pathology expert board: five years' experience of an extraordinary pathological diagnostic conundrum. (22nd June 2015) - Griggs, R; Noormohamed, S; Vella, J; Foy, C; Sanders, S; Novelli, MR; Shepherd, NA
Abstract : Introduction: Adenomatous polyps of the colon, especially of the sigmoid colon, can show epithelial misplacement into the submucosa. 1 Also termed pseudo-invasion, this feature can strongly mimic invasive adenocarcinoma. Recently described as the "diagnostic conundrum of the century", 2 it is recognised that the differential diagnosis of polyp cancer versus epithelial misplacement poses particular difficulty for pathologists. 3 A national Expert Board (EB) was established in 2009 to provide a consensus histopathological diagnosis for challenging cases. The aim of this study was to review the first five years of the BCSP EB and to assess its effectiveness in a very difficult diagnostic area. Method: A retrospective review was performed of all cases referred to the Expert Board in a five year period from its inception, in 2009, to 2013. Records were extracted from a prospectively maintained database, which included the opinion of the originating pathologist (s) and the results from each Board member. Levels of agreement between the originating pathologist (s) and between the three EB pathologists were then assessed using kappa statistics. Results: A total of 249 cases were analysed. In this period, the EB had an increase in referrals of 260%, from 20 in 2009 to 72 in 2013. Of the 249 cases, 200 (80.3%) demonstrated a EB three-way agreement, with a kappa score of 0.67, defined as substantial agreement. There were marked differences between the diagnoses of the originating pathologist (s) and the Board consensus; for instance a benign diagnosis was made in 30.6% of cases by the originating pathologist (s) compared with 80.3% by the EB. The overall local to EB kappa consensus score was 0.09, only just better than chance. Of the 131 submissions submitted with a definite diagnosis, 47% had their grading revised by the EB consensus. Conclusion: This study demonstrates a dramatic increase in referrals to the BCSP EB in its first five years. The diagnosis of the originating pathologist (s) was often at odds with the EB consensus and yet the Board demonstrated very good levels of agreement. The establishment of the Board is one of many successful developments in pathology associated with the introduction of cancer screening programmes and demonstrates the importance of expert opinion in difficult pathological diagnostic areas. Disclosure of interest: None Declared. References: Muto T, Bussey HJR, Morson BC. J Clin Pathol 1973; 26: 25–31 Shepherd NA, Griggs RKL. Mod Pathol2015; in press Loughrey MB, Shepherd NA. Histopathology 2015; 66: 66-77